THE EFEKTIVITAS MODEL PEMBELAJARAN DENGAN MEDIA BAHAN ALAM TERHADAP KEMAMPUAN BERPIKIR KREATIF ANAK: EFFECTIVITIVENESS OF LEARNING MODELS WITH NATURALS MEDIA ON THE CREATIVE THINGKING ABILITY OF CHILDREN - Novitayanti; Parwoto; Herlina (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to determine whether learning with natural media is effective in improving children's creative thinking skills in CGK Sumarorong Kindergarten. The research approach used is a quantitative approach with a Quasi-Experimental Design type of research. The population in this study was group B aged 5-6 years. The sample in this study was 7 children. The data collection technique used is descriptive statistical analysis and non-parametric statistical analysis. Based on the results of the study, it was concluded that the creative thinking ability of children before being treated in the form of learning with natural materials media and after being given treatment, was included in the category of developing according to expectations for the experimental group. While the control group is in the category of starting to develop. So that the effectiveness of the learning model with natural media on the creative thinking ability of children in CGK Sumarorong Kindergarten.